TIPE DAN LUAS DISTRIBUSI TUTUPAN VEGETASI BERDASARKAN ZONA SUHU MENGGUNAKAN CITRA LANDSAT 8 DI KAWASAN HUTAN LINDUNG KECAMATAN DOLO SELATAN - Hamka, Hamka; Adiputra, Herlangga (ForestSains, 2018)
Vegetation cover is closely related to temperature that causes the variation of temperature magnitude with a fairly high intensity. Meanwhile, surface temperature is affected by vegetation. This study aims to determine the type and the extent of vegetation distribution based on temperature zones using Landsat 8 imagery. It was carried out in the protected forest of South Dolo Sub-district, Sigi Regency, Central Sulawesi, Indonesia. The methodology includes unsupervised classification method and survey method. Data collection phase employs the techniques to obtain primary and secondary data, and data processing. The results indicate the relationship between vegetation cover and the changes in surface temperature, and the effect of the vegetation cover on the surface temperature of the protected forest in South Dolo Sub-district. The Landsat 8 image classification shows this area is dominated by tree with temperature of 17.3–22.2 ˚C, while the temperature of shrubs /open land is 22.3–31.7 ˚C. The relationship between temperature and vegetation cover is reflected from the value of y = 25.687 – 10.043x in trees and y = 2.980 + 3.000x in shrubs/open land with a coefficient of determination/R2 = 1, which indicates the extent of the area of vegetation cover (y) is affected by surface temperature (x).